If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+5)=3(5x-7)
We move all terms to the left:
3(x+5)-(3(5x-7))=0
We multiply parentheses
3x-(3(5x-7))+15=0
We calculate terms in parentheses: -(3(5x-7)), so:We get rid of parentheses
3(5x-7)
We multiply parentheses
15x-21
Back to the equation:
-(15x-21)
3x-15x+21+15=0
We add all the numbers together, and all the variables
-12x+36=0
We move all terms containing x to the left, all other terms to the right
-12x=-36
x=-36/-12
x=+3
| (6*8-7)+(5*8+1)=x | | 4x+1+61=90 | | 5k-5k=-7+k+6-2k | | 5y(-2)=17 | | -2x-28=3(x+4) | | 12=24(-h+3)-3h | | -7m-4m=0 | | 3(x+5=3(5x-7) | | 19x15=19 | | 12.4x+8.6x=126 | | 12(4x+8)=0.4(12x+6) | | 5(2m-4)+2m=16 | | 6(0.5x+2)+2x-4=4x+2 | | -29=1+3a | | 10p+10=80 | | 3x+8=-13+7x | | x-4x=x+1-5x | | 14.25x=27 | | 8x-30=140 | | -36=3x(-7) | | 24÷4x=3 | | 8x-30=160 | | 2x-28=3x+12 | | 4(9+x)=121 | | -6=12-4x+7x | | 8x-30=155 | | x/9-1=15 | | 63n−7=32n+5 | | 8x-30=150 | | -9x+6=-7x+14 | | x-1+4x+6=90 | | (6x+9)+(6x+9)=35+10x |